Implementasi Dashboard Akademik Bebasis Website Berdasarkan Instrumen Akreditasi Program Studi 4.0 - Roby Ari Putra; Khalid Khalid; Dwi Rolliawati (Systemic: Information System and Informatics Journal, 2021)
Accreditation activities aim to evaluate the quality and feasibility of an institution based on the data it has. The accreditation process requires supporting data sources from various documents and different databases, therefore requiring a system for a fast and efficient data collection and visualization process. One of the systems that can be used is a dashboard system and a data warehouse. In this study, the development and implementation of a data warehouse and dashboard system was carried out based on the guidelines for the Department Accreditation Instrument 4.0 (IAPS 4.0) from BAN-PT using the prototyping development method. From the implementation results, 38 quantitative indicators were obtained which can be visualized into the dashboard system. From the testing process using the requirements traceability matrix and functional testing, it was found that all test items successfully passed the test and this system can be used for the accreditation process based on IAPS 4.0 BAN-PT. With this system, it is hoped that the campus department can use it to carry out an independent evaluation process before or during the study program accreditation process.